Role of Actors in Policy Formulation Process in Development Plan for Land Transport Study Case in Tuban Regency - Anesia Ribka; Andy Fefta Wijaya (Indonesian Journal of Environment and Sustainable Development, 2013)
Related with policy formulation process in development plan, numbers of actors was involved into it. The roles of actors were matched with main duties and functions of each actor. Those actors were involved since public aspiration activity to formulation and socialization of policy. Every actor in policy making process has their own interest. Sometimes it might cause a conflict among the actors. Policy making process needed involvement from policy maker. To ensure the sustainability and success in transportation development in Tuban Regency, it should be determined by good policy. The policy formulation in local areas, as well as central government, was influenced by many actors and factors. In Tuban regency, the major role should be hold by Department of Transportation because it is a specific department in transportation field, and together with local development planning agency were formulate and implement the policy of transportation. However, the role of department of transportation was not prominent because of political factor and internal factor such as the lack of fund and human resources.   Kata Kunci: actors, policy, development, plan, land transport